The influence of pay-to-view television on professional cricket : professional cricket player perceptions - Adamson, James (2014)
Professional cricket in England and Wales has undergone a significant period of transformation during the last 20 years. The aim of this study is to identify the role that pay-to-view television has played during this period of transformation from the perspective of professional cricket players. Specifically, this research seeks to identify the influence of pay-to-view television on cricket governance, economics and culture, from the perspective of professional cricket players in England and Wales.